2021
DOI: 10.1007/s12274-021-3804-2
|View full text |Cite
|
Sign up to set email alerts
|

Laser-generated high entropy metallic glass nanoparticles as bifunctional electrocatalysts

Abstract: High entropy metallic glass nanoparticles (HEMG NPs) are very promising materials for energy conversion due to the wide tuning possibilities of electrochemical potentials offered by their multimetallic character combined with an amorphous structure. Up until now, the generation of these HEMG NPs involved tedious synthesis procedures where the generated particles were only available on highly specialized supports, which limited their widespread use. Hence, more flexible synthetic approaches to obtain colloidal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 108 publications
1
36
0
Order By: Relevance
“…Selective oxidation of Fe was not surprising due to its higher oxygen affinity. Similar element-specific surface oxidation has recently been reported for laser-generated Mn-rich high entropy alloy metallic glass nanoparticles, where the slight manganese oxide/hydroxide surface segregation has been observed, which increased with Mn content in the alloy [41].…”
Section: Variation Of the Initial Mixing State Of The Target And The Laser Pulse Durationsupporting
confidence: 84%
See 1 more Smart Citation
“…Selective oxidation of Fe was not surprising due to its higher oxygen affinity. Similar element-specific surface oxidation has recently been reported for laser-generated Mn-rich high entropy alloy metallic glass nanoparticles, where the slight manganese oxide/hydroxide surface segregation has been observed, which increased with Mn content in the alloy [41].…”
Section: Variation Of the Initial Mixing State Of The Target And The Laser Pulse Durationsupporting
confidence: 84%
“…They found that independent of the solvent, a combination of both solvent purification methods leads to oxidationminimized Fe-Rh nanoparticles, proven even by atom probe tomography, and no impact of the bound oxygen in the molecule of the organic solvent could be found. But Johny et al recently discovered that acetonitrile as dispersant leads to amorphous (metallic glass) nanoparticles if a quinary or senary alloy is ablated and discussed the role of solventdelivered carbon as glass morphology stabilizer [41]. This amorphization phenomenon was not observed for quinary alloy nanoparticles produced by lases ablation in ethanol [46].…”
Section: Variation Of the Initial Mixing State Of The Target And The Laser Pulse Durationmentioning
confidence: 99%
“…15,[72][73][74][75] When the synthesis duration and quenching time are even faster than those of HEAs or using easily glass-forming elements, metallic glass nanoparticles with a disordered atomic structure (lattice) can be formed. [76][77][78] For example, Glasscott et al 76 reported high-entropy metallic glass nanoparticles up to eight elements CoCrCuGdInMnNiV fabricated with precisely tunable stoichiometric ratios by the nanodroplet-mediated electrodeposition, which is an electroshock process with a feature time scale of ∼100 ms but at a much lower temperature (∼room temperature; Figure 2D,E). 76 The energy-dispersive X-ray mapping showed that these elements were distributed uniformly over the nanoparticles, which had calculated mixing entropy ΔS > 1.61 R, qualifying as high entropy mixing (Figure 2E).…”
Section: Ultrafast Shock Synthesismentioning
confidence: 99%
“…Similarly, other shock methods are also used to prepare HEA nanoparticles with different characteristics, such as microwave, 42,82 ultrasonication, 46 radiative shock heating, 41,83,84 and laser methods (Figure 3A). 16,43,77,85 For example, Qiao et al 42 fabricated the PtPdFeCoNi HEA nanoparticles uniformly distributed on reduced graphene oxide film via microwave energy (at 1800 K for several seconds) to realize high temperature for rapid synthesis of HEAs. Using highenergy acoustic cavitation in the ultrasonication process, NM precursors could be coreduced and transformed into alloy structures to synthesize multicomponent alloy nanoparticles by ultrasonication-assisted wet chemistry at room conditions.…”
Section: Other Shock-type Synthesesmentioning
confidence: 99%
See 1 more Smart Citation